Cervical spondylotic myelopathy: conservative versus surgical treatment after 10 years - Kadaňka, Zdeněk; Bednařík, Josef; Novotný, Oldřich; Urbánek, Igor; Dušek, Ladislav (European spine journal, 2011)
It is not known whether the results of decompressive surgery to treat the mild and moderate forms of spondylotic cervical myelopathy (CSM) are any better than those of a conservative approach. A 10-year prospective randomised study was performed. The objective of the study was to compare conservative and operative treatments of mild and moderate, non-progressive, or slowly progressive, forms of CSM. Sixty-four patients were randomised into two groups of 32. Group A was treated conservatively while group B was treated surgically. The clinical outcome was evaluated by modified JOA score, timed 10-m walk, score of daily activities recorded by video and evaluated by two observers blinded to the type of therapy, and by subjective assessment by the patients themselves. Seventeen patents died of natural, unrelated causes, during the follow-up. A total of 25 patients in the conservatively and 22 in the surgically treated group were used for the final evaluation. There was no statistically significant difference between both groups in mJOA score, in subjective evaluation by the patients themselves and in evaluation of video-recordings of daily living activities by two observers blinded to treatment mode. There was neither any difference found in the percentage of patients losing the ability to walk nor in the time taken to cover the 10-m track from a standing start. Comparison of conservative and surgical treatment in mild and moderate forms of CSM in a 10-year follow-up has not shown, on average, a significant difference in results. In both groups, patients get better and worse. According to the power analysis it is necessary admit that these results possess the low ability to answer definitely the question which treatment is better for the patients with a mild and moderate non-progressive CSM because of the low number of patients for the final evaluation and for clinically negligible differences between two compared arms. These findings can serve as a worthy odds-on hypothesis which needs the confirmation.
Keywords: dospělí; Female; Adult; výsledek terapie; ženské pohlaví; Disability Evaluation; komprese míchy; Spondylosis; lidé; Activities of Daily Living; chirurgická dekomprese; Decompression, Surgical; Treatment Outcome; krční obratle; následné studie; činnosti denního života; prospektivní studie; Follow-Up Studies; Male; progrese nemoci; spondylóza; Aged; Prospective Studies; Disease Progression; posuzování pracovní neschopnosti; lidé středního věku; Cervical Vertebrae; senioři; mužské pohlaví; Middle Aged; Spinal Cord Compression; Humans